Cosmological special relativity - Carmeli, Moshe (World Scientific, 2002)
Includes bibliographical references and index; This book presents Einstein's theory of space and time in detail, and describes the large-scale structure of space, time and velocity as a new cosmological special relativity. A cosmological Lorentz-like transformation, which relates events at different cosmic times, is derived and applied. A new law of addition of cosmic times is obtained, and the inflation of the space at the early universe is derived, both from the cosmological transformation. The relationship between cosmic velocity, acceleration and distances is given. In the appendices gravitation is added in the form of a cosmological general relativity theory and a five-dimensional unified theory of space, time and velocity. This book is of interest to cosmologists, astrophysicists, theoretical physicists, mathematical physicists and mathematicians.